Abundance of Meiofauna in the Surf Region of The Eastern Coast, Libya (Derna, Lathrun) - Hajir Alfurjani; Abeer Mohammed (AlQalam Journal of Medical and Applied Sciences, 2025)
During the summer of 2024, two study sites in eastern Libya were used to establish meiofauna diversity in the Southern Mediterranean Sea's near-shore sandy bottom surf region. Six taxa of floatable meiofauna (extracted from sediment samples by flotation), Nematoda and Foraminifera, were the most abundant. The other available taxa were Bivalve, Platyhelminthes, Gastropoda, and Ostracoda. Four non-floatable meiofauna taxa were encountered (Foraminifera, Bivalve, Gastropod, and Ostracoda). This low diversity of floatable and non-floatable meiofauna was possibly due to the strong wave action prevailing in the region and the adjacent deleterious anthropogenic activities. Meiofaunal diversity was higher in Derna than in Lathrun, possibly due to the higher dissolved phosphorus concentration during this season. The causes of the between-site differences in meiofaunal diversity are unclear, but differences in adjacent coastal anthropogenic activities might have had more impact on the interstitial habitat. New practical techniques for collecting and identifying the smaller meiofauna are needed.